Body mass index and partial remission in 119 children with type 1 diabetes—a 6-year observational study - Sokołowska-Gadoux, Magdalena; Jarosz-Chobot, Przemysława; Polanska, Joanna; Kalemba, Alicja; Chobot, Agata (Frontiers in Endocrinology, 2023)
Background/objective: This long-term study aimed to analyze associations between BMI Z-score, HbA1c and daily insulin requirement (DIR) and the prevalence and duration of partial remission (PR) in children and adolescents with type 1 diabetes (T1D).Methods: After retrieving retrospective data for 195 patients from their health records at 24, 48 and 72 months after T1D diagnosis the study group was comprised by 119 (57 girls) children with a complete dataset for all 6 years. PR was defined according to the ISPAD guidelines. Analyzes were carried out in the whole group and subgroups according the PR duration: no PR at all (NPR), PR lasting less than two years (PR<2), and PR at least two years (PR≥2).Results: PR was observed in 63% of patients (78.9% of overweight and 100% of obese patients). NPR patients showed the lowest mean initial BMI Z-score (-0.65±1.29 vs 0.02±1.42 (PR<2), p=0.01 and vs 0.64±1.43 (PR≥2), p=0.17). The dissimilarity in BMI across patients declined over time. Within NPR group initial mean BMI Z-score significantly increased within the first 2 years (unadjusted p<0.001) and remained constant afterwards. In PR<2 group, the highest increase of the BMI Z-score occurred after 4 years (p<0.001) and then decreased (p=0.04). In the PR≥2, the BMI Zscore slightly decreased within the first 2 years (p=0.02), then increased (p=0.03) and remained unchanged for the last two years. 6 years after T1D started, the mean DIRs do not differ among patient groups (ANOVA p=0.272).During 6 years of follow-up, PR occurred in almost 2/3 of the studied children including almost all overweight and obese children. We observed a gradual normalization of the BMI Z-score at the end of the follow-up. BMI Z-score increased slightly in children with no remission initially, but remained later constant until the end of observation. In both remitters groups, the increase of BMI Z-score appeared later, when the protective honeymoon period ended. Regardless of BMI Z-score, beta cell destruction process progresses and after 6 years, the DIR is similar for all patients.